Manajemen Strategis Kepala Sekolah dalam Pengembangan Lembaga Pendidikan Di SD Muhammadiyah 1 Pucanganom Sidoarjo - Muhammad Hambal Shafwan; M. fazlurrahman Hadi; Burhanuddin (STAI Muhammadiyah Paciran Lamongan, 2023)
This research was based on efforts to realize educational institutions that were consistent with superior qualifications as an achievement of the school’s vision and mission. The formulation of the problem of this thesis is first, how is the development of educational institutions in SD Muhammadiyah 1 Pucanganom Sidoarjo at this time, secondly how the implementation of strategic management of the principal in the development of educational institutions at SD Muhammadiyah 1 Pucanganom Sidoarjo, and third, what are the only factors that support and hinder the implementation of the principal's strategic management in the development of educational institutions in SD Muhammadiyah 1 Pucanganom Sidoarjo. This type of research was field research that collected primary data through in-depth interviews from the principal, and teachers in SD Muhammadiyah 1 Pucanganom Sidoarjo. Secondary data of this research were obtained from the literature and administrative file documents in SD Muhammadiyah 1 Pucanganom Sidoarjo. The results showed that the strategic management of the principle in SD Muhammadiyah 1 Pucanganom Sidoarjo uses the RIRE approach which translated as the strength of the implementation of the principal’s strategic management. This strength consisted of the values of religiosity, integrity, respect, and excellence which are grounded to all teachers and employees as well as students in SD Muhammadiyah 1 Pucanganom Sidoarjo.